2016
DOI: 10.1016/j.ecresq.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Do the effects of early childhood education programs differ by gender? A meta-analysis

Abstract: A meta-analysis was conducted to examine gender differences in the effects of early childhood education programs on children's cognitive, academic, behavioral, and adult outcomes. Significant and roughly equal impacts for boys and girls on cognitive and achievement measures were found, although there were no significant effects for either gender on child behavior and adult outcomes such as employment and educational attainment. Boys benefited significantly more from these programs than girls on other school ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 57 publications
2
38
1
Order By: Relevance
“…Magnuson et al. () provided a discussion of some of the components of center‐based education that could differently affect boys and girls. For example, Holmlund and Sund () reported that teachers respond more positively to children of the same sex.…”
Section: Discussionmentioning
confidence: 99%
“…Magnuson et al. () provided a discussion of some of the components of center‐based education that could differently affect boys and girls. For example, Holmlund and Sund () reported that teachers respond more positively to children of the same sex.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, probing the degree to which these effects may be explained by differences in cognitive and/or socio-emotional functioning is of particular use for generating knowledge about intervention impact fadeout and persistence (Bailey et al, 2017). Additional attention is also needed to understand the degree to which ECE’s impacts may be stronger—or weaker—for particular subgroups of children (Magnuson et al, 2016). In the Perry program evaluated in this study, for example, improvements in graduation rates and reductions in grade retention were driven entirely by girls, whereas effects on criminal activity, later-life income, and employment were driven by boys (Heckman et al, 2010; Schweinhart et al, 2005).…”
Section: Existing Evidence On Impacts Of Early Childhood Educationmentioning
confidence: 99%
“…Earlier reviews of universal preschool programs also find more beneficial effects for low SES students and no clear gender differences. Magnuson et al (2016) also find few gender differences in a review of mainly targeted programs.…”
Section: Introductionmentioning
confidence: 96%